Challenges Of Type Diabetic Foot Ulceration And Role Of Health Care Social Work In Saudi Arabia 2024 (The Review of Diabetic Studies, 2024)
Background Diabetic foot ulcers (DFUs) are a major health issue in Saudi Arabia, leading to significant, psychological, and physical burdens, often resulting in amputation, highlighting poor patient knowledge and gaps in healthcare professional practices. Healthcare Social Workers (HCSWs) play a crucial role by addressing these social determinants, bridging the gap in patient education, providing psychosocial support (especially post-amputation), connecting families to resources, advocating for systemic improvements, and improving the overall Quality of Life (QoL) for DFU patients, tackling issues from lack of awareness to financial strain and lack of proper footwear . Also role of Healthcare Social Work (HCSW) in DFU Management HCSWs address the holistic needs of patients, focusing on: Psycho-Social Support, education & empowerment , resource navigation , advocacy , quality of life improvement . Diabetic foot ulceration is an increasing problem worldwide with over 80% of amputations preceded by foot ulcers and little evidence of reduction in amputation rates in people with diabetes. Diabetic foot ulcers (DFUs) are common problems in diabetes.Aim of the study: To determining the challenges of Type diabetic foot ulceration and Role of Health Care Social Work in Saudi Arabia 2024.Method:  A cross-sectional, was conducted in  hospitals, in Saudi Arabia , within Multidisciplinary Diabetic Foot Clinics and/or Vascular Surgery Departments. to determining  the challenges of type diabetic foot ulceration and role of Health Care Social Work in Saudi Arabia, also a self-administered questionnaire was designed and has been send to the study participants, was performed between March 2024 and August 2024. Our total participants were (300).  Results: shows that most of the participants were (30.0%) in the age group 30-40 years, gender the majority of them were male (62.0%), education the majority of participant are University degree were (43.0%), number of children the majority of participant more than five were (39.0%), marital stats most of participants single were(45.0%).Conclusion: The burden of DFUs in LMICs requires comprehensive strategies. This shows that people’s daily, social, and personal lives, as well as their participation in several activities, were affected when diabetic patients presented with DFU. DFU can affect QoL, Moreover, this study deeply and social aspects but also the main roles of health care social work.